PENGELOLAAN KEUANGAN KOPERASI MENDUKUNG KEMANDIRIAN EKONOMI RAKYAT PADA PRA KOPERASI MAJU MAKMUR UNGARAN - Juli Ratnawati; Anna Sumaryati; Enny Susilowati Mardjono (Sekolah Tinggi Ilmu Ekonomi AMA, 2023)
In an organization, an important component in creating accountability from the organization is the financial report. The financial information presented by the organization serves as a foundation for consideration in making decisions and is an element in carrying out organizational accountability effectively. Cooperatives are the pillars of the Indonesian economy. The government strongly encourages the growth and development of cooperatives because cooperatives have a noble aim for the welfare of their members. This community service aims to assist and provide training in preparing cooperative financial reports to partners, namely Pra Koperasi Maju Makmur Semarang Regency so that they can independently manage financial documents and present their financial reports for the internal and external interests of the cooperative. The implementation method is by providing understanding to the management and members of cooperatives regarding the types of financial reports, knowledge of cooperative laws and how to prepare cooperative financial reports in a structured manner. The results of the community service show that the training participants understand the preparation of comprehensive cooperative financial reports.